Global Gene Expression Change Induced by Major Thoracoabdominal Surgery. Issue 6 (December 2017) - Allen, Casey J.; Griswold, Anthony J.; Schulman, Carl I.; Sleeman, Danny; Levi, Joe U.; Livingstone, Alan S.; Proctor, Kenneth G.
Abstract : Objective: To test the hypothesis that major thoracoabdominal surgery induces gene expression changes associated with adverse outcomes. Background: Widely different traumatic injuries evoke surprisingly similar gene expression profiles, but there is limited information on whether the iatrogenic injury caused by major surgery is associated with similar patterns. Methods: With informed consent, blood samples were obtained from 50 patients before and after open transhiatal esophagectomy or pancreaticoduodenectomy. Twelve cases with complicated recoveries (death, infection, venous thromboembolism) were matched with 12 cases with uneventful recoveries. Global gene expression was assayed using human microarray chips. A 2-fold change with a corrected P < 0.05 was considered differentially expressed. Results: In these 24 patients, 522 genes were differentially expressed after surgery; 248 (48%) were upregulated (innate immunity and inflammation) and 274 (52%) were downregulated [adaptive immunity (antigen presentation, T-cell function)]. Hierarchical clustering of the profile reliably predicted pre- and postoperative status. The within-patient change was 3.08 ± 0.91-fold. There was no measurable association with age, malignancy, procedure, surgery length, operative blood loss, or transfusion requirements, but was positively associated with postoperative infection (3.81 ± 0.97 vs 2.79 ± 0.73; P = 0.009) and hospital length of stay ( r = 0.583, P = 0.003). Venous thromboembolism and mortality each occurred in one patient, thus no associations were possible. Conclusions: Major surgery induces a quantifiable pattern of gene expression change that is associated with adverse outcome. This could reflect early impaired adaptive immunity and suggests potential therapeutic targets to improve postoperative recovery. Abstract : Supplemental Digital Content is available in the text